2009
DOI: 10.1073/pnas.0900957106
|View full text |Cite
|
Sign up to set email alerts
|

Implications for complex cognition from the hafting of tools with compound adhesives in the Middle Stone Age, South Africa

Abstract: Compound adhesives made from red ochre mixed with plant gum were used in the Middle Stone Age (MSA), South Africa. Replications reported here suggest that early artisans did not merely color their glues red; they deliberately effected physical transformations involving chemical changes from acidic to less acidic pH, dehydration of the adhesive near wood fires, and changes to mechanical workability and electrostatic forces. Some of the steps required for making compound adhesive seem impossible without multitas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
239
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 339 publications
(249 citation statements)
references
References 28 publications
4
239
0
1
Order By: Relevance
“…For Wadley et al (5), A consists of stone artifacts excavated from the Middle Stone Age site of Sibudu in southern Africa, which are about 70,000 years old. The heart of the inference is the argument B that takes us from features of A to the probable or necessary presence of C, in this case spears with hafted points.…”
Section: Technical System (Abc)mentioning
confidence: 99%
See 2 more Smart Citations
“…For Wadley et al (5), A consists of stone artifacts excavated from the Middle Stone Age site of Sibudu in southern Africa, which are about 70,000 years old. The heart of the inference is the argument B that takes us from features of A to the probable or necessary presence of C, in this case spears with hafted points.…”
Section: Technical System (Abc)mentioning
confidence: 99%
“…13 and 14), and still others apply theories of embodied cognition (15). Indeed, Wadley et al (5) themselves tap into a cognitive model of working memory in their argument for mental rotation (16). In the face of competing cognitive models, how does one judge?…”
Section: Cognitive Prerequisites (Efg)mentioning
confidence: 99%
See 1 more Smart Citation
“…More "mundane" or "domestic" uses of red ochre (derived from hematite, Fe 2 O 3 ) are known from the ethnographic record of modern hunter-gatherers, for instance, as (internal and external) medication, as a food preservative, in tanning of hides, and as insect repellent (3)(4)(5)(6)(7)(8)(9). Archeological studies have identified ochre powder as an ingredient in the manufacture of compound adhesives (10). Thus, the use of iron oxides for "symbolic" purposes should be viewed as a hypothesis that needs to be tested, rather than simply assumed.…”
mentioning
confidence: 99%
“…Notable and novel technological innovations first appear in southernmost region of south Africa at a time of environmental variability after 100,000 years ago for example. These include the heat treatment of flint to improve knapping precision (Brown et al 2009), new standardised and precise project point technology (Shea 2006), microlithic and compound technology (Brown et al 2012), complex adhesives demanding an understanding of chemical reactions (Wadley, Hodgskiss, and Grant 2009), and poisons (d 'Errico et al 2012). Novel precise and standardised beadworking, interpreted as evidence of large-scale networks, appears in northernmost Africa at around 80,000 years ago (Bouzouggar et al 2007).…”
Section: Archaeological Evidencementioning
confidence: 99%